2017
DOI: 10.1177/1741143217739361
|View full text |Cite
|
Sign up to set email alerts
|

Headteacher performance management in England: Balancing internal and external accountability through performance leadership

Abstract: This article reports on research into headteacher performance management in England. The English school system couples organisational autonomy with close scrutiny of educational outcomes. The management of the performance of headteachers is a central aspect of such a system. The research involved a systematic literature review and the collection of data via national surveys, expert interviews and case studies. The findings point to three overarching conditions essential for what we identify as 'performance lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
(20 reference statements)
1
13
0
Order By: Relevance
“…It is supported with the findings of the research conducted by Davies and Ellison (1997) in the UK whose findings show that head-teachers' performance is an important factor that enhances the internal efficacy of the institutions. Works of national and international scholars have contributed to the existing body of knowledge whose findings reported that head-teachers possess strong attitudes towards institutional better development (Al-Farsi, 2007;Anyagre, 2016;Deakins et al, 2005;DeJaeghere et al, 2009;Eddy-Spicer et al, 2019;Khan et al, 2009;Mwinyipembe & Orodho, 2014;Sarıçam & Sakız, 2014). Moreover, the results of this study are also aligned with the findings of the research planned by Adeyemi (2012).…”
Section: Discussionsupporting
confidence: 86%
“…It is supported with the findings of the research conducted by Davies and Ellison (1997) in the UK whose findings show that head-teachers' performance is an important factor that enhances the internal efficacy of the institutions. Works of national and international scholars have contributed to the existing body of knowledge whose findings reported that head-teachers possess strong attitudes towards institutional better development (Al-Farsi, 2007;Anyagre, 2016;Deakins et al, 2005;DeJaeghere et al, 2009;Eddy-Spicer et al, 2019;Khan et al, 2009;Mwinyipembe & Orodho, 2014;Sarıçam & Sakız, 2014). Moreover, the results of this study are also aligned with the findings of the research planned by Adeyemi (2012).…”
Section: Discussionsupporting
confidence: 86%
“…Prior to Covid-19, the impact of social disadvantage on wellbeing featured prominently within legislative and policy contexts across the UK (Children and Young People (Scotland) Act, 2014; Well-being of Future Generations (Wales) Act, 2015; What Works Centre for Wellbeing, 2020). For example, interagency collaboration is evident in person-centered, place-based initiatives (Dyson et al, 2014;Gilbert, 2017) such as the "nurturing city" in Glasgow, Scotland (March & Kearney, 2017, p. 237), the Full Service Extended Schools and Community Network programmes in Belfast, Northern Ireland, the introduction of Regional Improvement Collaboratives and Children's Neighborhoods in Scotland and designated Opportunity Areas and Children's Zones in England (Chapman, 2019;Easton et al, 2018). Additional funding is targeted at closing the opportunity gap between disadvantaged students and their more advantaged peers across the UK including the Pupil Premium (England and Northern Ireland), the Pupil Deprivation/Development grant (Wales), the Pupil Equity Fund (Scotland) and Attainment Scotland Fund.…”
Section: Research Contextmentioning
confidence: 99%
“…The terms 'performance management', 'appraisal', 'evaluation' and 'review ' are often used interchangeably (Eddy-Spicer et al, 2019). However, irrespective of terminology, headteacher performance management generally encompasses two dimensions: the development of headteacher capacity and accountability for performance (Davis et al, 2011;James and Colebourne, 2004).…”
Section: Performance Managementmentioning
confidence: 99%